The Influence Of Return On Assets (ROA), Return On Equity (ROE), And Debt To Equity Ratio (DER) On Stock Prices In Restaurant, Hotel And Tourism Companies Listed On The Indonesian Stock Exchange Period 2018 - Takhyudin, Yusup; Yuhaprizon, Yuhaprizon (Doktoral Ilmu Manajemen, Universitas Pasundan, 2024)
The purpose of this study is to examine the effect of Return on Assets (ROA), Return on Equity (ROE) and Debt to Equity Ratio (DER) simultaneously (together) on stock prices. as well as to test the effect of Return on Assets (ROA), Return on Equity (ROE) and Debt to Equity Ratio (DER) partially (each) on stock prices. This study has a population that is in the form of financial statements of hotel, restaurant and tourism industry group companies listed on the Indonesia Stock Exchange (IDX) in 2018 as many as 25 company units. This type of research is called cross-section, namely the financial statements taken can be one while there are many companies. Saturated sampling is one of the techniques carried out in this study, namely by sampling all members of the population, this is done because the population is relatively small. The company data samples obtained from the hotel, restaurant and tourism industry group were 25 company units. Secondary data in this study was obtained from the 2018 Indonesian Capital Market Directory (ICMD), namely in the form of financial reports published on the Indonesian Stock Exchange (IDX). The analytical tool used is the classical assumption test and hypothesis testing using the f-test simultaneously, partial t-test with a significance level of 5%. The results of the study show that return on assets, return on equity, debt to equity ratio either partially or simultaneously have no significant effect on stock prices.